2003
DOI: 10.35699/2675-5327.2003.21859
|View full text |Cite
|
Sign up to set email alerts
|

Comunidades de formigas (Hymenoptera: Formicidae) de serapilheira em áreas de cerrado “stricto sensu” em Minas Gerais

Abstract: The ant communities in both a native cerrado remnant in good preservation conditions and an anthropized area have been studied at Bom Despacho, Minas Gerais, Brazil. The Winkler technique was used to extract the litter ants, taking out 50 one-square meter litter samples in each area. Sixty-seven species were collected in the well-preserved cerrado area, and 45 in the anthropized one. Important differences were observed between the cerrado remnant and the degraded area, mainly regarding the generic and specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The abundance of the ant species is reduced in areas with wide distribution of larvae pits. The P. fallax group represents cosmopolitan ants with populous nests, which explains the high number of individuals sampled in the present study [37][38][39]. Thus, we highlight that Camponotus and Pheidole are important genera in the diet of Myrmeleon larvae in the Brazilian Cerrado.…”
Section: Discussionmentioning
confidence: 59%
“…The abundance of the ant species is reduced in areas with wide distribution of larvae pits. The P. fallax group represents cosmopolitan ants with populous nests, which explains the high number of individuals sampled in the present study [37][38][39]. Thus, we highlight that Camponotus and Pheidole are important genera in the diet of Myrmeleon larvae in the Brazilian Cerrado.…”
Section: Discussionmentioning
confidence: 59%
“…Studies have shown that arthropods, including free-feeding herbivorous and galling insects, respond to these characteristics differently between xeric and mesic habitats along the elevation gradient in the Serra do Cip o region, located in the southern portion of the Serra do Espinhaço (e.g. Araújo & Fernandes, 2003;Carneiro et al, 1995;Lara et al, 2002;Ribeiro et al, 1998). However, such studies have not yet been carried out for guilds of insects that exploit floral resources, such as bees.…”
Section: Introductionmentioning
confidence: 99%